Lead Isotopic Composition in Biogenic Certified Reference Materials Determined by Different ICP‐based Mass Spectrometric Techniques. Issue 2 (27th October 2014) - Ďurišová, Jana; Ackerman, Lukáš; Strnad, Ladislav; Chrastný, Vladislav; Borovička, Jan
<x xml:space="preserve">Abstract</x> This work presents data for the radiogenic Pb isotopic ratios (206Pb/207Pb and 208Pb/206Pb) in nine biogenic certified reference materials (NIST SRM 1515, 1566b, 1570a, 1573a, 1575a; BCR 100, BCR 101, BCR 670 and IAEA 359), which are suitable for analytical quality control in environmental research. The results were obtained using three different types of ICP‐based mass spectrometer (quadrupole‐based/magnetic sector field single‐collector ICP‐MS instruments and a multi‐collector ICP‐MS) and applying different mass bias correction procedures (calibrator‐sample bracketing and external Tl normalisation) with and without Pb separation from the matrix using ion exchange chromatography. In the majority of the samples, the measurements from all three of the ICP‐MS instruments were in agreement within ± 0.1%, despite the lower analytical precision of the single‐collector ICP‐MS instruments. We demonstrate that the presence of the sample matrix did not significantly influence the Pb isotopic ratios measured by magnetic sector field ICP‐MS, whereas the use of the two different mass bias corrections resulted in a systematic difference of 0.09% for the 208Pb/206Pb ratio.